Evaluation of medical costs associated with use of new oral anticoagulants compared with standard therapy among venous thromboembolism patients. (12th August 2014) - Amin, Alpesh; Jing, Yonghua; Trocio, Jeffrey; Lin, Jay; Lingohr-Smith, Melissa; Graham, John
Abstract: Objective: This study evaluated differences in medical costs associated with clinical end-points from randomized clinical trials that compared the new oral anticoagulants (NOACs), dabigatran, rivaroxaban, apixaban, and edoxaban, to standard therapy for treatment of patients with venous thromboembolism (VTE). Research design and methods: Event rates of efficacy and safety end-points from the clinical trials (RE-COVER, RE-COVER II, EINSTEIN-Pooled, AMPLIFY, Hokusai-VTE trial) were obtained from published literature. Incremental annual medical costs among patients with clinical events from a US payer perspective were obtained from the literature or healthcare claims databases and inflation adjusted to 2013 costs. Differences in total medical costs associated with clinical end-points for the NOACs vs standard therapy were then estimated. One-way and Monte Carlo sensitivity analyses were carried out. Results: A lower rate of major bleedings was associated with use of any of the NOACs vs standard therapy. Except for dabigatran, use of NOACs was also associated with a lower rate of recurrent VTE/death. As a result of the reduction in clinical event rates, the overall medical cost differences were −$146, −$482, −$918, and −$344 for VTE patients treated with dabigatran, rivaroxaban, apixaban, and edoxaban, respectively, vs patients treated with standard therapy. Conclusions: When any of the four NOACs are used instead of standard therapy for acute VTE, treatment medical costs are reduced. Apixaban is associated with the greatest reduction in medical costs, which is driven by medical cost reductions associated with both efficacy and safety end-points. Further evaluation may be needed to validate these results in the real-world setting.